Corporate governance and economic performance - Gugler, Klaus (Oxford : Oxford University Press, 2001)
This text presents evidence about corporate governance and performance in a large number of countries. It is the result of a collective research effort by the members of the European Corporate Governance Network (ECGN).
Includes bibliographical references and index.
oif 19/03/15
Loan
Keywords: Corporate governance; Performance -- Economic aspects